2021
DOI: 10.1001/jamanetworkopen.2021.17128
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Buprenorphine Induction in the Emergency Department for Treatment of Opioid Use Disorder

Abstract: IMPORTANCE Emergency departments (EDs) sporadically use a high-dose buprenorphine induction strategy for the treatment of opioid use disorder (OUD) in response to the increasing potency of the illicit opioid drug supply and commonly encountered delays in access to followup care.OBJECTIVE To examine the safety and tolerability of high-dose (>12 mg) buprenorphine induction for patients with OUD presenting to an ED. DESIGN, SETTING, AND PARTICIPANTSIn this case series of ED encounters, data were manually abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 42 publications
0
95
2
Order By: Relevance
“…We urge law enforcement departments to reconsider their policies to force overdose victims to the hospital when state or local policies or laws do not mandate this practice. Although there could be some benefits from transporting people who have just overdosed to emergency departments that have robust recovery support, medication-assisted treatment (e.g., buprenorphine induction), and other harm reduction programs (Chen et al,2020;Collins et al, 2021;Curran et al,2021;D'Onofrio et al, 2015;Herring et al,2021), most emergency rooms do not offer culturally competent services for people who have overdosed (Bergstein et al,2021;Biancarelli et al,2019;Chan Carusone et al,2019;Reddy et al,2021). However, the continued demonstrated public health efficacy of naloxone "take home programs" (McDonald et al,2017) point to how first responder "leave behind" naloxone programswhich involve providing kits on scene to the overdose victim, family, and/or friends of the person who overdosed-could greatly mitigate future overdoses and show early promise for connecting victims to treatment (Scharf et al,2021).…”
Section: Discussionmentioning
confidence: 99%
“…We urge law enforcement departments to reconsider their policies to force overdose victims to the hospital when state or local policies or laws do not mandate this practice. Although there could be some benefits from transporting people who have just overdosed to emergency departments that have robust recovery support, medication-assisted treatment (e.g., buprenorphine induction), and other harm reduction programs (Chen et al,2020;Collins et al, 2021;Curran et al,2021;D'Onofrio et al, 2015;Herring et al,2021), most emergency rooms do not offer culturally competent services for people who have overdosed (Bergstein et al,2021;Biancarelli et al,2019;Chan Carusone et al,2019;Reddy et al,2021). However, the continued demonstrated public health efficacy of naloxone "take home programs" (McDonald et al,2017) point to how first responder "leave behind" naloxone programswhich involve providing kits on scene to the overdose victim, family, and/or friends of the person who overdosed-could greatly mitigate future overdoses and show early promise for connecting victims to treatment (Scharf et al,2021).…”
Section: Discussionmentioning
confidence: 99%
“…Herring et al have recently shown that high-dose buprenorphine (high-dose induction dose defined as greater than 12 mg) is both efficacious and safe in treating patients with opioid use disorder in the ED. 14 Extended-release (ER) tramadol has been shown to be as effective as buprenorphine for treating opioid withdrawal in two randomized controlled trials. Doses up to 600 mg/day of tramadol ER were used successfully in one randomized controlled trial, but the drug was quickly tapered over one week during their residential treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These initiation doses differ from what is suggested by both SAMHSA and ASAM, which both recommend a lower initial BUP dose of 2–4 mg. 3 , 24 More recent ED literature has also shown that higher doses of BUP (>12 mg during an ED visit) in patients experiencing opioid withdrawal can be tolerated in select patients. 27 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Although 8 mg of BUP for withdrawal was the day 1 limit set by the Food and Drug Administration label for Suboxone (buprenorphine/naloxone), studies have ended day 1 of BUP on a higher total dose. 27 , 38 , 39 , 42 Although the ideal indications for and safety of higher day 1 doses of BUP in patients coming to the ED is under investigation, a higher maximum BUP dose may be beneficial not only for withdrawal relief but also for patients with barriers to follow‐up care such as prolonged wait time for postdischarge follow‐up or prior authorizations. 27 , 30 On the whole, variability in initial and maximum ED doses of BUP and the timing between doses in ED BUP initiation protocols underscore both the flexibility of BUP initiation across different EDs settings and a lack of consensus on best practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation